An Experimental Approach to Examine a Multi-Channel Multi-Hop Wireless Backbone Network - Taenaka, Yuzo; Tagawa, Masaki; Tsukamoto, Kazuya (Informatica, 2015)
This paper presents an experimental deployment of a multi-channel multi-hop wireless backbone network (WBN) with an OpenFlow-based traffic management method. Specifically, a set of APs, each of which uses a single but different channel, is connected by Ethernet and thus constructs a Virtual AP (VAP), thereby achieving a WBN with multi- ple channels. To exibly control traffic ows transmitted over a multi-channel multi-hop WBN, we propose a simple traffic management method based on the OpenFlow control. In the performance evaluation, we rst conduct a preliminary experiment as a lab scale and then deploy a 6-hop WBN enabling to provide the Internet access service in a conference (from proof-of-concept to a practical environment). Since the control messages are inherently transmitted with the introduction of OpenFlow, the way of isolation be- tween control plane and data plane will become a critical issue to actually deploy the proposed system for the Internet service. We additionally employ a wireless control network for the conference experiment. The experimental results show that the proposed WBN can increase the network capacity in accordance with the number of channels, thereby providing significant throughput performance for various applications.